FROM MICROFINANCE TO ‘‘GINTINGAN’’: REINVENTING LOCAL INSTITUTIONS FOR POVERTY REDUCTION IN INDONESIA - Saefullah, Kurniawan (PEOPLE: International Journal of Social Sciences, 2018)
Poverty has been acknowledged as a fundamental problem in development. It is so pervaded so the United Nations’s has put ‘no poverty’ as the first objective to be achieved in the Sustainable Development Goals (SDGs). As a 15thbiggest countries in the world in terms of Gross Domestic Product, Indonesia arehas been struggling in combating povertywith the increased proportion of inequality and most of its inhabitants are economically vulnerable. Although Microfinance has been believed as a tool to reduce poverty, however, various recent researcheson the microfinance impact on poverty reduction have shown pessimistic results. This paper discussesthe recent issues in the development figures of Indonesia, including the role of microfinance in poverty alleviation, which has been criticized and concluded by the discussion about an indigenous local institution of ‘Gintingan’ in rural area of West Java and how it has been contributing to Sustainable Community Development in Indonesia